Analisis Kandungan Gizi Mie dari Campuran Tepung Umbi Kano (Dioscorea alata L.) dan Tepung Rumput Laut (Eucheuma spinosum) Asal Wakatobi - Wa Ode Samine Iru; La Harimu; Haeruddin (Sains: Jurnal Kimia dan Pendidikan Kimia, 2022)
Research has been carried out with the title "Analysis of the Nutrient Content of Noodles from a Mixture of Kano Bulb Flour (Dioscorea alata L.) and Seaweed Flour (Eucheuma Spinosum) from Wakatobi". This study aims to make noodles from a mixture of canoe tuber flour and seaweed flour by knowing the ratio composition of the best noodle raw materials and to determine the nutritional content of noodles, both fat, ash, and water. The samples of this study were canoe tubers (Dioscorea alata L) and seaweed (Eucheuma spinosum). This research was conducted using proximate and organoleptic analysi methods. Based on the results of data analysis, it was concluded that the noodles were made with several types of comparisons of canoe tuber raw materials and seaweed flour, namely 95:5, 90:10, 85:15, 80:20, and 75:25. Noodles made with various comparisons were then carried out organoleptic tests with the results of hedonic test analysis from 20 panelists of noodles with the best quality being noodles with a ratio of 95:5. The results of the analysis of the nutritional content of noodles from the best organoleptic analysis are 95:5, dry noodles contain water of 4.19% and wet noodles have water and fiber contentof 35.44 % and 11,58%.